Values in The Book of Islamic Religious Education and Characteristics For First High School In Curriculum 2013: A Content Analysis - Munir Yusuf; Nur Rahmah; Nursyamsi Nursyamsi; Mirnawati Mirnawati; Firman Firman (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The rise of violence among students gives the impression that barren education gives birth to students with noble character. This research studies the contents of the Islamic Religious Education and Morals Education textbook for Junior High Schools (SMP), a student handbook. The main problem is what values are contained in the PAI SMP textbooks and their relevance to the realities of junior high school students' lives. Researchers analyzed three things: First, the prospect of Islamic religious education textbooks in solving the problems of adolescent life in junior high school. Second, values become the content of Islamic religious education textbooks in answering the problems of junior high school youth life. Third, Solutions to adolescent problems in junior high schools are offered through Islamic religious education textbooks Junior High School (SMP) level. It was found that the entire material for Islamic Religious Education textbooks in junior high schools contained five crucial issues: Tawhid, Morals, History, Tolerance, and Obedience. The five issues are broken down into various messages, all identified into 31 forms of messages, where messages about obedience and tolerance are the most significant frequency compared to other messages. Islamic Religious Education Textbooks for Junior High Schools published by the Ministry of Education and Culture in 2013 have met the standard criteria for aspects of Islamic knowledge that are the needs of students in junior high schools. Therefore, increasing the effectiveness of using Islamic Religious Education textbooks is recommended.